2007
DOI: 10.2164/jandrol.106.000760
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Results of Autologous Venous Grafts for Penile Morphological Reconstruction

Abstract: In order to evaluate the long-term results of autologous venous grafts, we present an overview of patients who underwent a procedure utilizing a venous patch from the deep dorsal vein with or without combination of the cavernosal vein in treating penile deformity. From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 32 publications
2
15
0
3
Order By: Relevance
“…Even though some studies described excellent results after grafting procedures, 26,35 others reported, in accordance with our observations, a reduced erectile function of patients after a grafting procedure. 21,23,27 Hsu et al 26 reported equivalent erectile function after venous grafting procedures in comparison to the preoperative situation in patients with PD and with congenital deviation after an average follow-up of 43 months (7 month to 10 years), whereas Kim et al 27 described a significantly reduced erectile function/rigidity after a grafting procedure with venous patches after a medium follow-up time of at least 1 year compared to simpler shortening procedures. Also in line with the results of our study, Kim et al 27 described a higher loss of sensation in patients after grafting procedure than after ST procedures even though differences in our study were statistically not significant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Even though some studies described excellent results after grafting procedures, 26,35 others reported, in accordance with our observations, a reduced erectile function of patients after a grafting procedure. 21,23,27 Hsu et al 26 reported equivalent erectile function after venous grafting procedures in comparison to the preoperative situation in patients with PD and with congenital deviation after an average follow-up of 43 months (7 month to 10 years), whereas Kim et al 27 described a significantly reduced erectile function/rigidity after a grafting procedure with venous patches after a medium follow-up time of at least 1 year compared to simpler shortening procedures. Also in line with the results of our study, Kim et al 27 described a higher loss of sensation in patients after grafting procedure than after ST procedures even though differences in our study were statistically not significant.…”
Section: Discussionsupporting
confidence: 91%
“…Even though some publications already report successful surgical treatment, long-term follow-up data especially with regard to the functional outcome remain scarce. 14,21,26,27 The aim of the present study was to evaluate and compare the selfreported long-term outcome and overall satisfaction in patients treated by either STs or a grafting procedure with TachoSil method (TM) at our institution. (See below for a detailed description of the surgical methods).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that autologous vein is an acceptable material for the grafting procedure in PD treatment (Hsu et al, 2007;Leungwattanakij, Bivalacqua, Yang, Hyun, & Hellstrom, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…Penile prosthesis implantation in patients with PD is a very effective procedure, with more than 90% of patients able to engage in penetrative sexual intercourse and 84% fully satisfied with cosmetic and functional outcome [61].…”
Section: Surgical Approachesmentioning
confidence: 99%